Network pharmacology to explore the novel anti-inflammatory mechanism of naringenin in intestinal ischemia/reperfusion injury - Hou, Min; Wang, Yanshun; Chen, Suheng; Tan, Zhiguo; Liu, Jie; Li, Xiaoxi; Han, Xiaoxia; Yang, Zaiqi; Leng, Yufang (Frontiers in Immunology, 2025)
IntroductionNaringenin (Nar), a common flavanone abundant in citrus fruits and tomatoes, is common in diets. Although Nar can alleviate intestinal ischemia/reperfusion injury (IRI), the exact anti-inflammatory mechanisms are unclear and require further study.MethodsIn this study, we employed a comprehensive research strategy that integrated network pharmacology analysis with both in vitro and in vivo experimental validations to systematically elucidate Nar’s anti-inflammatory mechanisms in intestinal IRI.ResultsNetwork pharmacology uncovered 88 common anti-inflammatory targets for Nar in intestinal IRI. Among these, TNF, IL6, AKT1, IL1B, TP53, STAT3, and PTGS2 were identified as hub genes. Validation experiments demonstrated that Nar induced anti-inflammatory responses through downregulating calprotectin, IL-1β, IL-6, and TNF-α, while promoting IL-10 secretion. Additionally, Nar pretreatment significantly downregulated PTGS2 and phosphorylated STAT3 (p-STAT3). Further mechanistic investigations were conducted using the YAP inhibitor verteporfin (VP) in vitro and in vivo. Nar pretreatment activated YAP, thereby enhancing its anti-inflammatory effects. Conversely, inhibiting YAP activation with VP increased p-STAT3 and enhanced inflammatory responses, diminishing Nar’s efficacy.ConclusionThis study demonstrated that Nar inhibited intestinal inflammatory responses by activating YAP, which suppressed p-STAT3 expression, and provided a theoretical basis for Nar’s clinical application in intestinal IRI.